Expression of CLEC3B in Oral Squamous Cell Carcinoma and its Association with Clinicopathological Features - Syeda Zehra Ahmed, Fouzia Shaikh, Shumaila Usman, Akhtar Ali, Santosh Kumar Sidhwani, Junaid Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral squamous cell carcinoma is one of the leading causes of cancer related morbidity worldwide. The socioeconomic status and clinicopathological parameters have predictive importance specifically for head and neck squamous cell carcinoma. Literature has reported various studies on CLEC3B, and its correlation with OSCC has yet to be explored. Aim: To examine the association of CLEC3B expression with the clinicopathological parameters in the blood and saliva of OSCC patients and healthy individuals. Methodology: This case-control study was conducted on 40 blood and 40 saliva samples recruited from Ziauddin University Hospital and the Abbasi Shaheed Hospital. Blood and saliva samples were taken from 20 OSCC patients as well as 20 healthy individuals as controls. Demographic details including age, gender, and habits were collected directly from participants on a proforma. RT-qPCR was carried out to determine the association of CLEC3B expression in the blood and saliva of OSCC patients and healthy individuals with clinicpathological parameters. Result: Significant expression was observed in blood and saliva samples of OSCC (p-value 0.001*). CLEC3B was significantly expressed in saliva samples with respect to pathological grading and staging of OSCC. Moreover the foldchange analysis was considerably underexpressed in both samples (saliva p-value 0.042, blood p-value 0.014).Whereas no significant association was found with respect to the habits, age and gender of patients. The significant expression of CLEC3B in saliva may improve the ability of clinicians to detect OSCC at an early stage and may help to reduce the mortality rate of patients. Conclusion: A significant association of salivary CLEC3B was observed with the staging and grading of OSCC and it was found that CLEC3B may have the potential to be used as a suitable biomarker for the detection and diagnosis of OSCC. This study could provide insight into ongoing evidence on the importance of CLEC3B in early detection of oral cancer. Furthermore, the salivary gene expression can be used to characterize tumor grading and staging. Keywords: CLEC3B, Biomarkers, Gene expression, Oral cancer, RT-qPCR, molecular diagnostics